(untitled) (Baghdad Science Journal, 2014)
The paper is devoted to solve nth order linear delay integro-differential equations of convolution type (DIDE’s-CT) using collocation method with the aid of B-spline functions. A new algorithm with the aid of Matlab language is derived to treat numerically three types (retarded, neutral and mixed) of nth order linear DIDE’s-CT using B-spline functions and Weddle rule for calculating the required integrals for these equations. Comparison between approximated and exact results has been given in test examples with suitable graphing for every example for solving three types of linear DIDE’s-CT of different orders for conciliated the accuracy of the results of the proposed method.